Analysis of the impact of environmental taxes, renewable energy, green finance, trade openness, and structural changes on CO2 emissions in Vietnam - Ngo , Thái Hưng; Nguyen , Thị Huỳnh Anh; Le , Thị Phương Thảo; Phan, Hoàng Tiến Đạt; Pham, Thuỳ Trang; Nguyen, Cao Phát (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
The study analyzes the impact of green finance (GF), renewable energy (REN), environmental taxes (TAX), trade openness (TRA), and structural changes (SER) on CO₂ emissions in Vietnam from 2000 to 2023 using wavelet analysis and wavelet quantile regression. The results uncover a bidirectional causal association between these indicators and CO₂ emissions in Vietnam. In addition, renewable energy positively affects environmental quality; environmental taxes, trade openness, and structural changes have negative environmental impacts; and green finance would contribute positively to the environment in the long run - term. Based on these findings - In light of these findings, we provide policy implications aligned with Vietnam’s practical context and sustainable development goals.